Analisis Usability Pada Aplikasi SatuSehatMenggunakan Mixed Methods - Abel Gilang Saputra; Ngurah Agus Sanjaya ER; I Made Satria Bimantara (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
SATUSEHAT mobile application is the official health application of the Ministry of Health of the Republic of Indonesia (Kemenkes RI). This application is a development of the previous application, PeduliLindungi, which only focused on handling the COVID-19 pandemic in 2020-2021. However, the focus of the SATUSEHAT app has been expanded. Some of its main focuses are accessing medical records, viewing vaccination status, and checking personal health status. Unfortunately, from several reviews, there are still many users who are not satisfied with their experience using this application, so this study aims to analyze the usability value using a combined method, of which two are Usability Testing and Post-Study System Usability Questionnaire. This research will involve 10 respondents, who will work on a short task, then answer a questionnaire to measure Usability Testing scores, and finally answer some questions to measure Post-Study System Usability Questionnaire scores. It is hoped that this research can help the developer of the application to see what aspects still have shortcomings, so that in the future it can be improved and developed again. Keywords: SATUSEHAT, Usability Testing, Post-Study System Usability Questionnaire